New Cixiidae from Eastern Polynesia: Oteana gen.nov. and Manurevana gen. nov. (Hemiptera: Fulgoromorpha) - Hoch, Hannelore (Zootaxa, 2006)
Two new genera are established to accommodate the cixiid species from the Society, Austral and Cook Islands formerly assigned to the genus Oliarus Stål: 1. Oteana gen.nov. with the type species Oteana euphranor (Fennah) comb.nov. from Tahiti, Oteana eurynome (Fennah, 1958) comb. nov.from Moorea, and Oteana gemellar (Fennah, 1958) comb. nov. from Rarotonga (Cook Islands); additionally, ten new Oteana species are described from the Society Islands: Oteana iaorana sp. nov., O. tiare sp. nov., O. aorai sp. nov., O. mato sp. nov., O. ata sp. nov., O. moana sp. nov., and O. pouvana sp. nov., all from Tahiti, as well as O. aimeho sp. nov. from Moorea, O. omai sp. nov. from Huahine, and O. temehani sp. nov. from Raiatea. 2. Manurevana gen. nov. with the type species Manurevana draconarius (Fennah, 1958) comb. nov. Notes on their ecology and distribution are given.